FEATURES OF CONSTRUCTION AND USE OF MODERN ACCESSIBLE TRANSMITTING SYSTEMS - Павлій, В. О.; Сардак, А. Г.; Макаров, О. М.; Степух, В. А. (Science-based technologies, 2019)
The basic tendencies of the development of the technology of receiving and transmitting devices of any destination are substantiated. The analysis of the basic electrical characteristics of transmission systems is carried out. The basic design requirements for receiving and transmitting devices are defined. It is shown that the main operational requirements include: time of continuous operation, switching on and off, operational reliability (coefficient of combat capability, earnings for failure); climatic conditions (limits of operating temperatures, humidity, atmospheric pressure); the minimum cost of serial production and operation; maintainability, maximum service safety. It is substantiated that in order to obtain the output of a transmitter, quite a lot of power is often connected in parallel by several devices, the amount of power in space or the use of special bridges are added, which, along with an increase in power level and increased reliability of the transmitter, increase the stability of the generated oscillations. The solution to the problem of increasing the capacity of radio transmitters has led to a sharp increase in the volume of equipment. The main parameters that formulate the technical requirements for receivers are sensitivity, selectivity, dynamic range. They affect the precision characteristics and electromagnetic compatibility of the radio engineering system in which the receiver is used. Control of technical parameters of electronic equipment is carried out in order to determine the conformity of its technical characteristics to the required. The main quantitative characteristics for reliability evaluation are the probability of failure-free operation, work failure and readiness ratio. Elements of the high-frequency path require qualitative harmonization, because there may be overvoltage’s, leading to breakdowns and overheating of contacts. The safe operation of modern transceiver systems requires timely control of the technical condition.